Поверхневе розсiювання носiїв струму i поверхневi електроннi стани - Sologub, S. V.; Bordenjuk, I. V.; Tegenkamp, C.; Pfn¨ur, H. (Publishing house "Academperiodika", 2019)
Experimental researches of the charge carrier scattering at Mo(110) and W(110) surfaces atomically clean or covered with a hydrogen (deuterium) monolayer with the participation of surface electronic states are considered. In addition, the scattering mechanisms of charge carriers in spin-polarized surface electronic states in Bi(111) epitaxial nanofilms with the atomically clean surface or the surface covered with magnetic and nonmagnetic adatoms to low coverages are discussed.